Christian Leadership in 3D - Peter Williams (Scandinavian Journal for Leadership & Theology)
This paper combines my previously published 3D-model of spirituality in general, and Christian spirituality in particular, with a constructivist understanding of leadership, to define and explore Christian leadership as serving followers by exercising a virtue-orientated rhetorical influence over their spirituality in a way that flows from the leader’s own spirituality as a follower of Christ. I also explore how Christian spirituality offers leaders and followers resources for mitigating against the abuse of leadership.